Linear Energy Transfer Incorporated Spot-Scanning Proton Arc Therapy Optimization: A Feasibility Study - Li, Xiaoqiang; Ding, Xuanfeng; Zheng, Weili; Liu, Gang; Janssens, Guillaume; Souris, Kevin; Barragán-Montero, Ana M.; Yan, Di; Stevens, Craig; Kabolizadeh, Peyman (Frontiers in Oncology, 2021)
Purpose: To integrate dose-averaged linear energy transfer (LETd) into spot-scanning proton arc therapy (SPArc) optimization and to explore its feasibility and potential clinical benefits. Methods: An open-source proton planning platform (OpenREGGUI) has been modified to incorporate LETd into optimization for both SPArc and multi-beam intensity-modulated proton therapy (IMPT) treatment planning. SPArc and multi-beam IMPT plans with different beam configurations for a prostate patient were generated to investigate the feasibility of LETd-based optimization using SPArc in terms of spatial LETd distribution and plan delivery efficiency. One liver and one brain case were studied to further evaluate the advantages of SPArc over multi-beam IMPT. Results: With similar dose distributions, the efficacy of spatially optimizing LETd distributions improves with increasing number of beams. Compared with multi-beam IMPT plans, SPArc plans show substantial improvement in LETd distributions while maintaining similar delivery efficiency. Specifically, for the liver case, the average LETd in the GTV was increased by 124% for the SPArc plan, and only 9.6% for the 2-beam IMPT plan compared with the 2-beam non-LETd optimized IMPT plan. In case of LET optimization for the brain case, the SPArc plan could effectively increase the average LETd in the CTV and decrease the values in the critical structures while smaller improvement was observed in 3-beam IMPT plans. Conclusion: This work demonstrates the feasibility and significant advantages of using SPArc for LETd-based optimization, which could maximize the LETd distribution wherever is desired inside the target and averts the high LETd away from the adjacent critical organs-at-risk.